2019
DOI: 10.21203/rs.2.12165/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trends in prevalence and correlates of intimate partner violence against women in Zimbabwe, 2005-2015

Abstract: Background: Intimate partner violence (IPV) is a widespread problem affecting all cultures and socioeconomic groups. This study explored the trends in prevalence and risk factors associated with IPV among Zimbabwean women of reproductive age (15-49 years) from 2005-2015. Methods: Data from the 2005/2006, 2010/2011 and 2015 Zimbabwe Demographic and Health Survey (ZDHS) on 13,409 women (survey year: 2005/2006; n=4,081), (survey year: 2010/2011; n=4,411) and (survey year: 2015; n=4,917) were analyzed. Multiple lo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(10 reference statements)
2
2
0
Order By: Relevance
“…Poverty is considered one of the risk factors of domestic violence (Jewkes, 2002). In line with prior studies (Babu & Kar, 2009; Martin et al, 1999; Mukamana et al, 2020), the present study also found that the likelihood of spousal violence against women was 46% lower in the richest wealth quintile than in the poorest quintile.…”
Section: Discussionsupporting
confidence: 92%
“…Poverty is considered one of the risk factors of domestic violence (Jewkes, 2002). In line with prior studies (Babu & Kar, 2009; Martin et al, 1999; Mukamana et al, 2020), the present study also found that the likelihood of spousal violence against women was 46% lower in the richest wealth quintile than in the poorest quintile.…”
Section: Discussionsupporting
confidence: 92%
“…Housewives were 18.062 times more likely to suffer from violence than those who were employed, and women younger than thirty years old were 23.045 times most likely to face violence. This result was consistent with a study conducted in Zimbabwe [16]. Unlike these results, the levels of education of women's and their husband's were the most significant risk factors for violence in Iran [14].…”
Section: Discussionsupporting
confidence: 91%
“…In southwest Ethiopia, the life-time prevalence of IPV of physical or sexual or both was 64.7% [2], and in southern brazil 56% reported to have experienced the problem [3]. Similarly, in Iran, the prevalence of physical, sexual and emotional violence was 16.4, 18.6 and 44.4%, respectively [14], while IPV studies in Zimbabwe and Ethiopia showed 15, 30%, respectively [15,16]. In contrast to our study; these articles are studied over a longer period and this may have led to higher prevalence of IPV.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have shown that women's age (Mukamana et al, 2020), their education level (Erten & Keskin, 2018;Ghislandi et al, 2020), economic and financial empowerment status (Abramsky et al, 2019;Akilova & Marti, 2014;Khalid & Choudhry, 2021;Raj et al, 2018), socioeconomic status (Ackerson & Subramanian, 2008;Mukamana et al, 2020;Stöckl et al, 2021), exposure to mass media (Rahman et al, 2013), and place of residence (Garg et al, 2021;Mukamana et al, 2020) are important predictors of IPV. Women who violate hypergamy norms (Roychowdhury & Dhamija, 2021) or whose mothers have been victims of IPV are also more likely to face IPV (Garg et al, 2021;Khalid & Choudhry, 2021;Mondal & Paul, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%